FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN SUBJEK PAJAK DALAM MELAKUKAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN - Atik Yunawati (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
The aim of this research to analyze influence of SPPT, sanction, service of duration and lease to compliance of lease subject in doing payment of PBB and also dominant variable have an effect on to compliance of lease subject in doing payment of PBB. This research represents research of survey. Source of data use primary data that is data and questioner of secondary. Technique intake of sampling purposive sample, that is in chosen sample fully pursuant to consideration of researcher alone regarding equipment of data, clarity of data, available and also of data to be collected for this research. Amount of taken sample 88 people of subject lease. Criterion of Sample is lease subject which have done arrears in payment of PBB residing in country sides in district of Mojolaban owning ranking 5 under. Technique analyzes data use doubled linear regression, test of t, test F and coefficient of determination (R2). Result of data analysis obtained by SPPT and sanction tcount > ttable. Both there is influence which is significant among SPPT and also sanction has an effect on to Compliance of Subject lease in doing payment of PBB. Service of lease and duration to compliance of subject lease value of significances (p-value) > 0,005. Meaning Ho accepts and Ha refused by its meaning do not there are influence among service of lease to compliance of subject lease in doing payment of PBB. Fcount > Ftable hence Ho refused to mean Ha accepted by that is there is influence among SPPT, Sanction, Service of lease and Duration to Compliance of Subject lease in doing Payment of PBB. Analysis Data got by R2 60, 9%. Meaning influence of SPPT, Sanction, Service of lease and duration to compliance of subject lease in doing payment of PBB and the rest influenced by other variable which do not check by its research variable. Conclusion of research for example SPPT have an effect on to compliance of taxes subject in doing payment of PBB. Sanction have an effect on to compliance of taxes subject in doing payment of PBB. Service of taxes do not have an effect on to compliance of taxes subject in doing payment of PBB. Duration do not have an effect on to compliance of taxes subject in doing payment of PBB. Dominant variable have an effect on to compliance of taxes subject in doing payment of PBB is Sanction. Keywords: SPPT, Sanction, Service of lease, Duration to Compliance of Subject Lease